3m-10=(4m-5)

Simple and best practice solution for 3m-10=(4m-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-10=(4m-5) equation:


Simplifying
3m + -10 = (4m + -5)

Reorder the terms:
-10 + 3m = (4m + -5)

Reorder the terms:
-10 + 3m = (-5 + 4m)

Remove parenthesis around (-5 + 4m)
-10 + 3m = -5 + 4m

Solving
-10 + 3m = -5 + 4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-4m' to each side of the equation.
-10 + 3m + -4m = -5 + 4m + -4m

Combine like terms: 3m + -4m = -1m
-10 + -1m = -5 + 4m + -4m

Combine like terms: 4m + -4m = 0
-10 + -1m = -5 + 0
-10 + -1m = -5

Add '10' to each side of the equation.
-10 + 10 + -1m = -5 + 10

Combine like terms: -10 + 10 = 0
0 + -1m = -5 + 10
-1m = -5 + 10

Combine like terms: -5 + 10 = 5
-1m = 5

Divide each side by '-1'.
m = -5

Simplifying
m = -5

See similar equations:

| (2w+5)(2w-5)= | | 50+y=x | | 4(2k+2)-9=4(k-2)-1 | | x-53=8 | | -4(5t-5)+8t=3t-3 | | 2(2k+5)+5k=2(3k+4) | | 235-6x=39x+15 | | 6x^5+x^4-15x^3=0 | | 4m+25+3[5+2(3m-15)-5]= | | x^2-kx+121=0 | | 4y+5=-3(2y-5) | | 36x^2+169=0 | | 3(3f+5)-10f=3(2f-5)+2 | | 3-4n=2n-15 | | 5x+15=-115-10x | | 10x-63=-3 | | 3=m+2 | | -5(4t-4)+6t=4t-5 | | 12(c-6)=2(x-9) | | 4x+2=28.4 | | (x+2)(-x+1)+(x-3)(x+2)=0 | | 2-5x=11-8x | | 20=6x+8 | | 7x-29=27 | | 11x^2+81=0 | | 12x-12-6x-9=3 | | 2c-4=9c-11 | | 5y=-2x+12 | | P=2q+10 | | 3x-1=13x-111 | | 58=27-e | | 3x-6-8+12x=x+10 |

Equations solver categories